The Monument to Micaela Bastidas (1967-1969), a symbol of the vindication of the rights woman during the Agrarian Reform - Esquivel Ortiz, Omar (2020)
The Monument to Micaela Bastidas (Monumento a Micaela Bastidas), despite its peripheral locationwithin Cercado de Lima district, is currently part of the public sculpture works. It was a strictly municipal project, developed during the first Revolutionary Government of the Armed Forces (1968-1975), a period of ideolo-gical exaltation, where the image of Túpac Amaru II was adopted as a symbol of national vindication and the image of Micaela Bastidas was reduced to a heroine mother, with no known face. Therefore, in this article we will review the discursive rediscovery María Roqué Barriach projected in the monument of the heroine, as a symbolic instrument of female struggle and freedom. She sought to project this, from her position as the only female councilor of the municipality of Lima, representative of the National Liberation Front.